Pulmonary Hypertension in Systemic Sclerosis - Cullivan, Sarah; Cronin, Eleanor; Gaine, Sean (Seminars in Respiratory and Critical Care Medicine, 2024)
Systemic sclerosis is a multisystem connective tissue disease that is associated with substantial morbidity and mortality. Visceral organ involvement is common in patients with systemic sclerosis and occurs independently of skin manifestations. Pulmonary hypertension (PH) is an important and prevalent complication of systemic sclerosis. The clinical classification of PH cohorts conditions with similar pathophysiological mechanisms into one of five groups. While patients with systemic sclerosis can manifest with a spectrum of pulmonary vascular disease, notable clinical groups include group 1 pulmonary arterial hypertension (PAH) associated with connective tissues disease, PAH with features of capillary/venous involvement, group 2 PH associated with left heart disease, and group 3 PH associated with interstitial lung disease. Considerable efforts have been made to advance screening methods for PH in systemic sclerosis including the DETECT and ASIG (Australian Scleroderma Interest Group) composite algorithms. Current guidelines recommend annual assessment of the risk of PAH as early recognition may result in attenuated hemodynamic impairment and improved survival. The treatment of PAH associated with systemic sclerosis requires a multidisciplinary team including a PH specialist and a rheumatologist to optimize immunomodulatory and PAH-specific therapies. Several potential biomarkers have been identified and there are several promising PAH therapies on the horizon such as the novel fusion protein sotatercept. This chapter provides an overview of PH in systemic sclerosis, with a specific focus on group 1 PAH.
Keywords: systemic sclerosis; pulmonary vascular disease; pulmonary hypertension; DETECT